Tax Structures and Economic Growth: A Study of Asian Countries (Journal of Entrepreneurship and Business, 2025)
This study aims to analyse the impact of total tax revenue and its structures on GDP per capita growth in 31 Asian countries. We estimate the results using the Static Panel Fixed Effects (within) regression with Driscoll and Kraay’s Standard Errors. The results suggest that increases in total tax revenue, taxes on income, profit and capital gain (direct taxes), and taxes on goods and services (indirect taxes) are associated with lower GDP per capita growth in Asian countries. In contrast, this study finds a significant and positive impact of taxes on property (other taxes), while labor taxes show an insignificant but positive impact on growth. We conclude that property taxes have a positive potential to sustain and promote higher growth, and the policymakers should consider to reduce both taxes on income and goods and services to encourage productivity and generate more consumption, which can stimulate economic growth in Asian countries.
Keywords: Array; Array; Array